Government of Meghalaya Annual Plan 2005-2006 - Planning Commission (Planning Commission, 2005)
Background and General Characteristics: Meghalaya first came into being as an Autonomous State within the Slate of Assam on the 2nJ April. 1970 and comprised of the two erstwhile Districts of Assam, viz: the United Khasi & Jaintia Hills District and the Garo Hills District. the Autonomous Stale was upgraded into a full Hedged Slate with effect form the 21s1 January. 1972. the Stale covers a geographical area of 22.429 Sq. Kins approximately . Il is one of the smallest Stales in India and is strategically located in the North-East between 25"" 5” and 26"" 10"" North Laiitudes and between 98"" 47"" and 97"" 47"" East Longitudes. It is a strip of land spread along the northern boundary of Bangladesh and it is bounded by that country on the South as well as on the West. the length of the International boundary is 423 Kins and the State is surrounded on the other sides by Assam. the land surface of the Slate mostly comprised of hills and table lands with the hills sloping gently towards Assam on the north but rather steeply and abruptly towards Bangladesh on the south.
Draft Proposals